Multi‐institutional analysis of stereotactic body radiotherapy for sarcoma pulmonary metastases: High rates of local control with favorable toxicity. Issue 5 (25th June 2020) - Baumann, Brian C.; Bernstein, Karen De Amorim; DeLaney, Thomas F.; Simone, Charles B.; Kolker, James D.; Choy, Edwin; Levin, William P.; Weber, Kristy L.; Muniappan, Ashok; Berman, Abigail T.; Staddon, Arthur; Hartner, Lee; et al.
Abstract: Background/Objectives: Oligometastatic sarcoma pulmonary metastases (PM's) are traditionally treated with resection and/or chemotherapy. We hypothesize that stereotactic body radiotherapy (SBRT) is an effective, safe alternative to surgery that can achieve excellent local control (LC) with a favorable toxicity profile. Methods: Patients treated with SBRT for sarcoma PM's from 2011 to 2016 at Massachusetts General Hospital and the University of Pennsylvania were included. Median dose was 50 Gy. Patients underwent computed tomography (CT) or positron emission tomography/CT Q3 months post‐SBRT. Results: 44 patients with 56 separate PM's were treated with SBRT. Median age was 59 (range 19‐82). 82% received prior chemotherapy, 66% had prior pulmonary resections (range, 1‐5 resections), and 32% received prior thoracic radiotherapy. Median lesion size was 2.0 cm (range, 0.5‐8.1 cm). Median follow‐up was 16 months and 25 months for patients alive at last follow‐up. Overall survival at 12 and 24 months was 74% (95% confidence interval [CI], 67%‐81%) and 46% (95% CI, 38%‐55%). LC at 12 and 24 months was 96% (95% CI, 93%‐98%) and 90% (95% CI, 84%‐96%). LC and overall survival did not differ based on age, gender, histology, fractionation, lesion location, or size ( P > .05). Three developed Common Terminology Criteria for Adverse Events version 4 grade‐2 chest‐wall toxicities; one had grade‐2 pneumonitis. Conclusions: In the first multi‐institutional series on SBRT for sarcoma PM's, SBRT has excellent LC and is well‐tolerated. SBRT should be considered as an alternative/complement to resection.